Lymphocyte Subpopulations in the Healthy Human Lacrimal Gland and Their Variations With Age and Sex, Systematic Review 1960–2023 - Claudia M. Trujillo‐Vargas; Luisa María Rendón‐Macías; Ronald Yamil Paredes Guerrero; Cinta S. dePaiva; Jaiberth Antonio Cardona‐Arias (Immunity, Inflammation and Disease)
ABSTRACT Background Immunosenescence has been associated with an imbalance in the lacrimal functional unit and histopathological changes in exocrine glands, especially in women. Objective To define the main lymphocyte subpopulations in the human lacrimal gland and their variations with age and sex, according to scientific articles published between 1960 and 2023. Methods A systematic review was performed on PubMed, ScienceDirect, and Google Scholar. The PRISMA 2020 guidelines were applied for the search and selection of studies. The methodological quality was evaluated with the STROBE guidelines. A meta‐analysis of three selected articles dichotomizing lymphocytic infiltrates according to age group was also performed. Results We selected 20 observational studies, including 774 healthy individuals (722 cadavers). The articles evaluated the lymphocyte infiltration with hematoxylin and eosin staining, immunohistochemistry and immunofluorescence. There was high variability in the criteria to define the apparently human lacrimal and to quantify the lymphocytic infiltration. There was an underrepresentation of individuals younger than 40 years (12.6%), and female sex (38.9%). Three articles reported an association of age and sex with lymphocytic infiltration in the healthy lacrimal gland, while two articles did not. Plasma cells were the most abundant lymphocyte subpopulation in the healthy lacrimal gland, including IgA‐containing plasma cells. B cells were reported to be very scarce in the LG in two articles. In the meta‐analysis of three selected articles, no statistical difference in lymphocytic infiltration was found between individuals younger and older than 60. Conclusion There is the need of further observational studies, better defining the study design, with similar representation across sex and ages to ascertain what are the changes of lymphocytic composition in the lacrimal gland related to age and sex. Further studies are also needed to assess the dynamics of lymphocytic populations in a more detailed manner using cutting‐edge methodologies such as single‐cell sequencing or transcriptomics. Trial Registration PROSPERO 2023 CRD42023435653 Available from: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023435653.